2009
DOI: 10.1096/fj.08-122192
|View full text |Cite
|
Sign up to set email alerts
|

Functional implications of the influence of ABCA1 on lipid microenvironment at the plasma membrane: a biophysical study

Abstract: The ABCA1 transporter orchestrates cellular lipid homeostasis by promoting the release of cholesterol to plasmatic acceptors. The molecular mechanism is, however, unknown. We report here on the biophysical analysis in living HeLa cells of the ABCA1 lipid microenvironment at the plasma membrane. The modifications of membrane attributes induced by ABCA1 were assessed at both the outer and inner leaflet by monitoring either the lifetime of membrane inserted fluorescent lipid analogues by fluorescence lifetime ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 52 publications
4
42
0
Order By: Relevance
“…Indeed, Landry et al ( 30 ) have reported that, through its ATPase-related functions, ABCA1 expression alters the general packing of the PM by generating more loosely packed microdomains. This fi nding is in agreement with a recent study by Zarubica et al ( 31 ) reporting that analysis of the partitioning of dedicated probes in PM-vesiculated blebs allowed visualization of ABCA1 partitioning into the liquid disordered-like phase and corroborated the idea that ABCA1 destabilizes the lipid arrangement at the PM. Their fi nding supports the concept that ABCA1 plays a pivotal role in controlling transversal and lateral lipid distribution at the PM and positions the effl uxes of cholesterol from the cell membrane to the redistribution of the sterol into readily extractable membrane pools.…”
Section: Control Under Lipoprotein Deprivation Incorporation Of [supporting
confidence: 92%
“…Indeed, Landry et al ( 30 ) have reported that, through its ATPase-related functions, ABCA1 expression alters the general packing of the PM by generating more loosely packed microdomains. This fi nding is in agreement with a recent study by Zarubica et al ( 31 ) reporting that analysis of the partitioning of dedicated probes in PM-vesiculated blebs allowed visualization of ABCA1 partitioning into the liquid disordered-like phase and corroborated the idea that ABCA1 destabilizes the lipid arrangement at the PM. Their fi nding supports the concept that ABCA1 plays a pivotal role in controlling transversal and lateral lipid distribution at the PM and positions the effl uxes of cholesterol from the cell membrane to the redistribution of the sterol into readily extractable membrane pools.…”
Section: Control Under Lipoprotein Deprivation Incorporation Of [supporting
confidence: 92%
“…ABCA1, as reported here, is the first ATP-binding cassette transporter to be shown to mediate substrate flux bidirectionally. It has previously been shown that overexpression of ABCA1 in cells alters lipid packing at PM (58,59) and creates outward membrane curvatures where apoA-I binds (7). Here we show that in the absence of sterol acceptors, ABCA1 deficiency causes cholesterol accumulation at the PM.…”
Section: Discussionmentioning
confidence: 99%
“…42 Although the activities of both ABC transporters in the foam cells were affected by the acidic challenge, the stronger reduction in the function of ABCA1 could be explained by its predominant location at the cell membrane surface, 43 which may have affected its stability when directly exposed to an acidic environment. A potential effect of acidic pH on modifying the charge polarization of the plasma membrane and its lipid arrangement not only could have reduced the ionic transport capability of the ABCA1 transporter protein 44,45 but also could have partially impaired the nonmediated aqueous diffusion of cholesterol. Because the plasma membrane seems to be the primary location for ABCA1-mediated apoA-I lipidation, 46 and apoA-I binding to ABCA1 requires membrane bending, 47 a pH-induced switch of the physical properties and spatial geometry of the plasma membrane probably causing dysfunctional lipid rafts that contain ABC transmembrane transporters, 48 or restricting the docking of several ligands, 49 may also compromise the functionality of ABCA1 protein.…”
Section: Discussionmentioning
confidence: 99%